Hubungan antara Kecemasan dan Motivasi Belajar pada Siswa Sekolah Menengah Atas (SMA) - Grace, Viona; Kartasasmita, Sandy (Lembaga Yasin AlSys, 2025)
Education has an important role in developing students‘ abilities, but significant changes in the education system, such as curriculum changes, and academic requirements often put pressure on students so that it can trigger anxiety and have an impact on students’ learning motivation. This study aims to determine the relationship between anxiety and learning motivation in high school students. The method used was a quantitative method involving 206 high school student participants based on purposive sampling. This study used the spearmen corellation method and the results showed that there was no relationship between anxiety and learning motivation of high school students. The correlation test results obtained an r value of -0.017 and p 0.814> 0.05. The results of the difference test using mann whitney and obtained there are differences in anxiety based on gender and differences in learning motivation based on grade level. The results of this study are expected to be useful for future researchers in conducting research with similar variables and useful for teachers to develop learning methods that can reduce student anxiety and can increase student learning motivation.